Identification of nuclear valosin-containing-protein-like as a target of anti-nuclear autoantibodies in systemic sclerosis - Zeng, Zitao; Miske, Ramona; Scharf, Madeleine; Denno, Yvonne; Ott, Anthonina; Brakopp, Stefanie; Teegen, Bianca; Stöcker, Winfried; Siegert, Elise; Saschenbrecker, Sandra; Probst, Christian; Komorowski, Lars (Frontiers in Medicine, 2025)
ObjectiveTo identify the target antigen of an anti-nuclear autoantibody (ANA) from a patient with a suspected systemic autoimmune disease and to study the autoantibody’s clinical association.MethodsThe index patient serum was screened for autoantibodies using indirect immunofluorescence assay (IFA) and line blots (membrane strips coated with parallel lines of different purified antigens). Immunoprecipitation with fixed HEp-2 cells followed by SDS-PAGE and MALDI-TOF mass spectrometry was used to identify the autoantigen, which was verified by competitive inhibition experiments, recombinant HEK293 cell-based IFA, and Western and line blots based on the recombinant antigen. The prevalence of autoantibodies against this antigen was studied in 693 patients with systemic autoimmune rheumatic diseases (SARD) and 150 healthy controls.ResultsThe index patient serum displayed a homogeneous nucleolar staining pattern on HEp-2 cells and monkey liver by IFA but did not react with 27 known nuclear antigens. Nuclear valosin-containing-protein-like (NVL) was identified as the ANA target antigen. Preincubation with recombinant NVL abolished the reactivity of the patient serum with HEp-2 cells in IFA. Additionally, the patient serum reacted with recombinant NVL in cell-based IFA and Western blot analysis, whereas sera from 15 healthy controls were nonreactive. Using line blots coated with recombinant NVL, anti-NVL autoantibodies were exclusively found in four out of 378 patients with systemic sclerosis, but neither in 315 patients with other SARD nor in 150 healthy controls.ConclusionThese findings indicate that autoantibodies against NVL may be a suitable marker to help narrowing the serological gap in systemic sclerosis.